The Polypyrimidine Tract-binding Protein Is Required for Efficient Dengue Virus Propagation and Associates with the Viral Replication Machinery - Anwar, Azlinda (American Society for Biochemistry and Molecular Biology, 2009)
The polypyrimidine tract-binding protein (PTB) functions primarily as an IRES trans-acting factor in the propagation of hepatitis C virus and picornaviruses. PTB interacts with secondary structures within the 3′- and 5′-untranslated regions of these viral genomes to mediate efficient IRES-mediated viral translation. PTB has also been reported to bind to the untranslated region of the single-stranded RNA dengue virus (DENV), suggesting a similar function for PTB in flaviviruses. Indeed small interfering RNA-mediated PTB knockdown inhibited the production of infectious DENV, and this inhibition was specific to PTB knockdown and not due to a nonspecific anti-viral state. In fact, PTB depletion did not inhibit the production infectious yellow fever virus, another flavivirus. Nevertheless, whereas PTB knockdown led to a significant decrease in the accumulation of DENV viral RNAs, it did not impair translation. Moreover, PTB was shown to interact with the DENV nonstructural 4A protein, a known component of the viral replication complex, and with the DENV genome during infection. These data suggest that PTB interacts with the replication complex of DENV and is acting at the level of viral RNA replication.